First report of two distinct phytoplasma species, ‘Candidatus Phytoplasma cynodontis’ and ‘Candidatus Phytoplasma asteris,’ simultaneously associated with yellow decline of Wodyetia bifurcata (foxtail palm) in Malaysia - Naderali, N.; Nejat, Naghmeh; Tan, Yee How; Vadamalai, Ganesan (American Phytopathological Society, 2013)
The foxtail palm (Wodyetia bifurcata), an Australian native species, is an adaptable and fast-growing landscape tree. The foxtail palm is most commonly used in landscaping in Malaysia. Coconut yellow decline (CYD) is the major disease of coconut associated with 16SrXIV phytoplasma group in Malaysia (1). Symptoms consistent with CYD, such as severe chlorosis, stunting, general decline, and death were observed in foxtail palms from the state of Selangor in Malaysia, indicating putative phytoplasma infection. Symptomatic trees loses their green and vivid appearance as a decorative and landscape ornament. To determine the presence of phytoplasma, samples were collected from the fronds of 12 symptomatic and four asymptomatic palms in September 2012, and total DNA was extracted using the CTAB method (3). Phytoplasma DNA was detected in eight symptomatic palms using nested PCR with universal phytoplasma 16S rDNA primer pairs, P1/P7 followed by R16F2n/R16R2 (2). Amplicons (1.2 kb in length) were generated from symptomatic foxtail palms but not from symptomless plants. Phytoplasma 16S rDNAs were cloned using a TOPO TA cloning kit (Invitrogen). Several white colonies from rDNA PCR products amplified from one sample with R16F2n/R16R2 were sequenced. Phytoplasma 16S rDNA gene sequences from single symptomatic foxtail palms showed 99% homology with a phytoplasma that causes Bermuda grass white leaf (AF248961) and coconut yellow decline (EU636906), which are both members of the 16SrXIV ‘Candidatus Phytoplasma cynodontis’ group. The sequences also showed 99% sequence identity with the onion yellows phytoplasma, OY-M strain, (NR074811), from the ‘Candidatus Phytoplasma asteris’ 16SrI-B subgroup. Sequences were deposited in the NCBI GenBank database (Accession Nos. KC751560 and KC751561). Restriction fragment length polymorphism (RFLP) analysis was done on nested PCR products produced with the primer pair R16F2n/R16R2. Amplified products were digested separately with AluI, HhaI, RsaI, and EcoRI restriction enzymes based on manufacturer's specifications. RFLP analysis of 16S rRNA gene sequences from symptomatic plants revealed two distinct profiles belonging to groups 16SrXIV and 16SrI with majority of the 16SrXIV group. RFLP results independently corroborated the findings from DNA sequencing. Additional virtual patterns were obtained by iPhyclassifier software (4). Actual and virtual patterns yielded identical profiles, similar to the reference patterns for the 16SrXIV-A and 16SrI-B subgroups. Both the sequence and RFLP results indicated that symptoms in infected foxtail palms were associated with two distinct phytoplasma species in Malaysia. These phytoplasmas, which are members of two different taxonomic groups, were found in symptomatic palms. Our results revealed that popular evergreen foxtail palms are susceptible to and severely affected by phytoplasma. To our knowledge, this is the first report of a mixed infection of a single host, Wodyetia bifurcata, by two different phytoplasma species, Candidatus Phytoplasma cynodontis and Candidatus Phytoplasma asteris, in Malaysia.